Benteng Terakhir: Peran Orang Tua dalam Melindungi Anak dari Bahaya Minuman Oplosan (Studi Kasus di Desa Pakamban Laok): (STUDI KASUS DI DESA PAKAMBAN LAOK) - Afifah, Muru’atul; Khafifah, Khafifah (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2024)
This study aims to describe the parental role in addressing adolescent delinquency caused by the consumption of adulterated beverages in Pakamban Laok Village, as well as to identify the supporting and inhibiting factors of this role. A qualitative approach was used with data collection through observation and interviews with parents of victims and involved adolescents. The results showed that parents act as leaders, supervisors, advisors, and friends to their children in addressing this issue. Support from the village environment through positive activities such as Shalawat Banjari, sports, and other religious activities is a significant supporting factor. In addition, the adolescents' awareness of the negative impacts of consuming adulterated beverages after a tragic incident also becomes an internal factor that drives behavioral change. However, peer influence, negative environmental views, lack of parental attention, the influence of social media, and adolescents' curiosity become inhibiting factors that need to be considered. This study concludes that the parental role is crucial in the prevention and handling of cases of adolescent consumption of adulterated beverages, but these efforts need to be supported by the surrounding environment and various related parties